Benjamin Clarke Marsh papers - Marsh, Benjamin Clarke, 1877-1952.
Correspondence, memoranda, minutes, articles, extracts, legislative documents, press releases, reports, speeches, pamphlets, scrapbooks, and clippings primarily concerning Marsh's service as executive secretary of the People's Lobby. Legislative issues of interest to the lobby included agriculture, cartels, commerce, conservation of natural resources, disarmament, housing, postwar planning and reconstruction, railroads, taxation, and unemployment. Correspondents include John Dewey, James Couzens, Harold L. Ickes, and Henry Cantwell Wallace.
Lobbyist and reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Couzens, James, -- 1872-1936 -- Correspondence; Dewey, John, -- 1859-1952 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Wallace, Henry Cantwell, -- 1866-1924 -- Correspondence; People's Lobby; Agriculture; Cartels; Commerce; Conservation of natural resources; Disarmament; Housing; Railroads; Reconstruction (1914-1939); Reconstruction (1939-1951); Taxation; Unemployment; Lobbyists; Reformers